2019
DOI: 10.1016/j.beth.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Is Heightened Disgust Propensity Truly a Risk Factor for Contamination-Related Obsessive-Compulsive Disorder?

Abstract: Disgust propensity (DP) has been conceptualized as a stable personality trait that confers risk for contamination-related OCD (C-OCD). However, the extent to which DP leads to the subsequent development of C-OCD is unclear. In fact, the presence of C-OCD might lead to an increase in DP rather than the inverse. The present study was aimed to test this hypothesis in a large clinical sample of OCD patients (≥ 21 years of age) with (C-OCD; n = 56) and without (NC-OCD; n = 103) contamination-related symptoms that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
(51 reference statements)
0
12
1
Order By: Relevance
“…Although disgust by some participants was reported during symptoms from the other OCD symptom dimensions, and to some extent during symptoms of SAD and GAD, it was most strongly related to symptoms within the contamination dimension. Previous studies have found a relatively weak relationship between disgust proneness, measured at the trait-level via self-report questionnaires, and the overall severity of OCD symptoms in clinically referred youth and adult samples [22,30]. The difference between these and the present findings can be partly attributed to our use of an interview-based assessment of emotion involvement during OCD symptoms and of OCD at the dimensional level.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although disgust by some participants was reported during symptoms from the other OCD symptom dimensions, and to some extent during symptoms of SAD and GAD, it was most strongly related to symptoms within the contamination dimension. Previous studies have found a relatively weak relationship between disgust proneness, measured at the trait-level via self-report questionnaires, and the overall severity of OCD symptoms in clinically referred youth and adult samples [22,30]. The difference between these and the present findings can be partly attributed to our use of an interview-based assessment of emotion involvement during OCD symptoms and of OCD at the dimensional level.…”
Section: Discussioncontrasting
confidence: 99%
“…This association is also found in clinical and nonclinical samples of youth, with changes in disgust sensitivity during OCD treatment being positively correlated with reductions in OCD symptoms [14,22,28,29]. However, as disgust proneness/sensitivity is also correlated with symptoms of anxiety, and as anxiety symptoms also tend to decrease during OCD treatment, the extent to which disgust plays a primary or secondary (to anxiety) role in OCD remains unclear [30].…”
Section: Introductionmentioning
confidence: 92%
“…Together, this may represent the implementation of the immobilization without fear state, through a neuroception of safety [29], that, in the polyvagal theory, is believed to require a co-activation of the NA and the DMNX fibers. The co-activation of myelinated NA fibers would assure a sense of safety given by the awareness of one's own bodily state, that could be, or promote, a portal to self-compassion [79][80][81][82][83][84][85][86][87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the study design was not able to take into account the complex nature of longitudinal data as not all variables were assessed at both time points, and these shortcomings should be addressed in future studies (e.g., by using multilevel modeling). Fifth, asking participants to retrospectively recall their pre-COVID-19 levels of AS-physical concerns, DP, and DS may introduce some level of error from recall bias and should be considered when interpreting the results (Melli et al, 2019). Sixth, the transdiagnostic constructs investigated in the current study are not an exhaustive list of all potentially relevant factors that could predict COVID-19 distress (e.g., health anxiety; Horenstein et al, 2019).…”
Section: Limitations and Future Directionsmentioning
confidence: 98%